The effect of over-based calcium sulfonate detergent additives on white etching crack (WEC) formation in rolling contact fatigue tested 100Cr6 steel. (May 2019) - Richardson, A.D.; Evans, M.-H.; Wang, L.; Ingram, M.; Rowland, Z.; Llanos, G.; Wood, R.J.K.
Abstract: Over-based calcium sulfonate (OBCaSul) additives in oils are considered potentially critical in driving WEC formations, this 'driving' effect being unclear. Rolling contact fatigue testing of 100Cr6 steel using FE8 and PCS Micro-Pitting-Rig lubricated with oils containing varying OBCaSul concentrations have been conducted, tested samples being analysed using serial sectioning, Thermal desorption analysis (TDA) to measure hydrogen diffusion, and SEM/EDX of the tribofilms formed. Results show that OBCaSul concentration appears to affect WEC formation propensity, a reversal relationship of formations being shown between test rigs. Evidence shows oils containing OBCaSul form thick Ca dominated tribofilms, potentially promoting hydrogen diffusion and WEC formations in the FE8 rollers, where thinner ZnS tribofilms on the FE8 raceways may demote hydrogen diffusion and WEC formations. Highlights: Over-based calcium sulfonate concentration affected WEC formation propensity. Reversal relationship of number of WEC formations between the tests rigs used. Positive link between hydrogen and over-based calcium sulfonate concentration. Thick Ca dominated films may promote hydrogen diffusion and WEC formations. Thinner ZnS film may demote hydrogen diffusion and WEC formations.